The Theoretical and Philosophical Basics of Islamism and Turkism in Ali Bay Huseinzada’s View - Alakbarli, Faig (Scholarya Demo Journal of Ruby, 2018)
he article reflects A.Huseynzada’s ideas of “Turkism, Islamism and Modernity”. The study shows the reason of his opinion on the unity of the ideas of Turkism and Islamism. Moreover, it reveals the theoretical and philosophical reasons for the defense of A.Huseynzada’s idea of “Ottoman Turkism”. The article shows that with the promotion of the ideas of “Turkism, Islamism and modernity” and “Ottoman Turkism” A.Huseinzada in fact opposed the idea of Azerbaijan Turkism and played a role of impetus in the formation of the theoretical and philosophical foundations of national idea of Azerbaijan (Azerbaijanism). It is not accidental that the tricolor flag of the Azerbaijan Democratic Republic was adopted on the basis of A. Huseinzada’s ideas. The article introduces A. Huseinzada as a prominent thinker in Azerbaijan as well as in the entire Turkic world.